Grape Pomace: A Review of Its Bioactive Phenolic Compounds, Health Benefits, and Applications - Janice da Conceição Lopes; Joana Madureira; Fernanda M. A. Margaça; Sandra Cabo Verde (Molecules)
The wine industry generates high amounts of waste, posing current environmental and economic sustainability challenges. Grape pomace, mainly composed of seeds, skins, and stalks, contains significant amounts of bioactive compounds and constitutes the main solid residue of this industry. Various strategies are being explored for its valorization, from a circular economy perspective. This review provides an updated overview of the composition of grape pomace from winemaking, highlighting sustainable methodologies for extracting phenolic compounds and their potential health benefits, including antioxidant, antimicrobial, antidiabetic, cardioprotective, antiproliferative, anti-aging, and gut health properties. Furthermore, this review explores the potential applications of this agro-industrial waste and its extractable compounds across the food, cosmetic, and pharmaceutical sectors.